Study on freshness quality and post-harvest loss of Hilsa (Tenualosa Ilisha) during marketing in Mymensingh town, Bangladesh - Dilip Chandra Ray; Md. Abu Zafar; AKM Nowsad Alam; Zubaida Parveen Patwary (Journal of Fisheries, 2015)
An investigation was conducted to know the freshness quality and associated post-harvest loss of hilsa, if any, transported to Mymensingh from the major landing centers through Cox’s Bazar-Chittagong (route A) and Barguna-Chandpur (route B) routes for a period of July to October 2012. The average environmental temperature of the wholesale and retail markets was 30.7 °C and 30.6 °C where the body temperature of hilsa was 4.5 °C (route A) and 4.7 °C (route B), respectively. The Freshness quality of hilsa was assessed using sensory defects points (DPs) that eventually gave rise to numerical values ‘1’ being the freshest and ‘5’ being the worst quality. The DPs of hilsa were found 2.0, which reveal that the fishes were in excellent conditions, i.e., there was no significant post-harvest loss even during retail sale. DPs on arrival and at wholesale in July, September and October were significantly different after auction and during retail sale (p<0.05), and in August differed significantly only during retail sale (p<0.05). It was observed that hilsa transported to Mymensingh from Barguna-Chandpur were better in quality than those transported from Cox’s Bazar-Chittagong. The reason behind this finding was not studied and this needs to be elucidated through further research.